Structural validity and internal consistency of an outcome measure to assess self-reported educator capacity to support children with motor difficulties - Cahill, Peter T.; Missiuna, Cheryl A.; DeCola, Cindy; Dix, Leah; Campbell, Wenonah N. (Frontiers in Education, 2023)
Partnering for Change (P4C) is a school-based occupational therapy service intended to build the capacity of educators to support children with motor difficulties. Aims This paper describes the development of the Partnering for Change Educator Questionnaire and evaluates its structural validity and internal consistency.The P4C Educator Questionnaire was completed by 1,216 educators four times across two years. Data from the initial time point were analysed via exploratory factor analysis (n = 436). Subsequently, Cronbach's alpha and mean interitem correlations were calculated. Finally, the proposed factor structure was confirmed by testing it against data from times two through four using confirmatory factor analysis (n = 688).A three-factor structure was evident and confirmed in hypothesis testing. The factor structure was interpretable according to the framework for building educator capacity used in this study. Internal consistency was high, with the total scale outperforming each subscale.Deleted: As part of a previous evaluation of P4C, a novel outcome measure of educator capacity was developed and administered. … A novel measure of educator self-reported capacity to support students with motor difficulties demonstrated structural validity and internal consistency. We currently recommend use as a complete scale accompanied by additional validation research.